Kualitas Air Sungai di Wilayah Yogyakarta Tahun 2008 - Sigid Sudaryanto; Sri Muryani (Poltekkes Kemenkes Yogyakarta, 2008)
Rivers as water body, for Yogyakarta’s people who are living nearby are used as one of the clean water sources to fulfill their daily needs. This study was aimed to understand and reveal the measurement of some field parameters as well as the laboratory ones of five rivers which crossing Yogyakarta. There were three measuring points for each observed river. The results showed that for following parameters: i.e. BOD, DO, pH, TSS, and temperature; the mea-surement still meet the standards stated by the government regulation No. 20/1990 about the tresholds for water quality of type B water. Those findings may be affected by the aeration process generated by small basins existed in some places, and also by the dilution process caused from additional debit of small rivers which ended at the rivers. However, as the MPN coliform was very high and had not fulfilled the requisite, it showed an indication that the rivers are contaminated by human excreta and so that they are not safe for clean water source.